2021
DOI: 10.1002/ijc.33464
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein biomarkers for early detection of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis, mainly due to late diagnosis at advanced tumor stages. In this study, we aimed to identify plasma protein biomarkers for early detection of PDAC. Totally, 135 PDAC patients (early PDAC, Stage I/II, n = 71; advanced PDAC, Stage III/IV, n = 64), 13 benign lesions/chronic pancreatitis patients and 72 healthy individuals, with corresponding plasma samples from a case‐control study in Sweden were included. A proximity extension assay was used to detect 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…The main strength of our study is the inclusion of a relatively large number of patients with advanced PDAC, and the Olink PEA method used. Today, >800 articles have described this method, including more than 120 studies of patients with cancer, but only four studies of patients with PDAC [23,24,43,44]. With results from 737 samples from 363 patients, we confirmed IL-6 as a prognostic marker in PDAC; moreover, we described other proteins that had previously been reported in relation to PDAC to also have prognostic capabilities.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The main strength of our study is the inclusion of a relatively large number of patients with advanced PDAC, and the Olink PEA method used. Today, >800 articles have described this method, including more than 120 studies of patients with cancer, but only four studies of patients with PDAC [23,24,43,44]. With results from 737 samples from 363 patients, we confirmed IL-6 as a prognostic marker in PDAC; moreover, we described other proteins that had previously been reported in relation to PDAC to also have prognostic capabilities.…”
Section: Discussionsupporting
confidence: 53%
“…This sequence can then be quantified using quantitative real-time PCR (qPCR) [21,22]. We, and others, have demonstrated that this method can identify protein panels that could be useful for early diagnosis of PDAC [23,24]. In our previously published study, we found two protein indices for the identification of patients with PDAC from patients with non-malignant pancreatic diseases and healthy individuals.…”
Section: Introductionmentioning
confidence: 98%
“…However, CA19-9 also gives false positive results in benign pancreaticobiliary diseases [ 14 , 15 ]. Several studies reported a number of non-invasive diagnostic and/or prognostic markers of pancreatic cancer that have been tested alone or in combination, such as: CA125, CEA, CEACAM1, MUC1, MIC1/GDF15, REG3A/PAP1, PKM2 and AXL, as well as auto-antibodies, fecal microbiome signatures and myeloid-derived suppressor cells [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Yet, the clinical utility of these markers remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…This panel can detect PC in plasma samples obtained from patients with unclassified stages (I–IV) of PC and shows prognostic potential . However, it remains unclear whether the ComB-CAN panel can detect early-stage (I/II) PC, given that early detection ability is the most important function of any cancer biomarker. …”
Section: Introductionmentioning
confidence: 99%